2013
DOI: 10.1055/s-0033-1350710
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Apocynin in a Mouse Model of Chemically-Induced Colitis

Abstract: Apocynin, a constituent of Picrorhiza kurroa, successfully inhibits NADPH oxidase and shows promise as an anti-inflammatory drug. Now, we report anti-inflammatory effects of apocynin in an experimental colitis model induced by dextran sulfate sodium as well as the effects on the mediators involved in this process. Apocynin reduced the colitis induced in mice by administration of 5 % dextran sulfate sodium during 7 days. Mice were fed a control diet or a diet supplemented with 2 % of apocynin or 2 % of rutin. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…This study has demonstrated for the first time, the potential for cooked ASP spears to mitigate colonic mucosal damage and promote mucosal healing after exposure to an inflammatory insult; an effect which is likely a result of its high RUT content. The beneficial effects of RUT on colonic inflammation have been demonstrated previously , and is shown to be due in part to the anti‐inflammatory, antioxidant, and colon barrier protective effects of its microbial‐derived metabolite, quercetin . In this study, we have demonstrated that the beneficial effects observed with purified dietary RUT can be partly obtained through consumption of a cooked RUT‐rich food which enhances the physiological and clinical relevance of our findings.…”
Section: Discussionsupporting
confidence: 76%
“…This study has demonstrated for the first time, the potential for cooked ASP spears to mitigate colonic mucosal damage and promote mucosal healing after exposure to an inflammatory insult; an effect which is likely a result of its high RUT content. The beneficial effects of RUT on colonic inflammation have been demonstrated previously , and is shown to be due in part to the anti‐inflammatory, antioxidant, and colon barrier protective effects of its microbial‐derived metabolite, quercetin . In this study, we have demonstrated that the beneficial effects observed with purified dietary RUT can be partly obtained through consumption of a cooked RUT‐rich food which enhances the physiological and clinical relevance of our findings.…”
Section: Discussionsupporting
confidence: 76%
“…One study has demonstrated TSPO ligand induced mitochondrial stabilization and ROS reduction in a mouse model of inflammatory bowel disease (Issop et al, ), while others demonstrate diffuse TSPO upregulation (Bernards et al, 2015; Wu, Briley, & Tao, ). Studies of the colon and brain have separately demonstrated the pivotal role NOX‐2 derived ROS has in inflammatory disease progression (Mouzaoui et al, ; Stolk et al, ; Marín et al, ). Thus, Nox‐2‐TSPO interactions may be the key to understanding TSPO's natural role as a cellular activity and inflammation regulator throughout the body.…”
Section: Discussionmentioning
confidence: 99%
“…NADPH oxidase inhibitor apocynin significantly inhibited the OTA-induced mesangial cytotoxicity and apoptosis. Several studies have demonstrated that apocynin has therapeutic effect on multiple animal disease model including chemically-induced colitis in mice [28], testicular ischemia-reperfusion injury in rats [29], bleomycin-induced lung fibrosis in rats [30], Cyclosporine A-Induced hypertension and nephrotoxicity in rats [31], established alcoholic steatohepatitis rat model [32], and contrast-induced nephropathy in the diabetic rats [33]. Therefore, these findings indicate that the concentrations of OTA used in this cellular toxicological study are reasonable and effectively induce mesangial cell cytotoxicity via a NADPH oxidase-derived ROS-mediated pathway.…”
Section: Discussionmentioning
confidence: 99%